Kedudukan Hukum Harta Pailit Sebagai Aset yang Dirampas Negara dalam Perkara Tindak Pidana Korupsi - M. Rizky Aldila; Dian Ayu Pratiwi (CV. Green Publisher Indonesia, 2025)
In practice, the application of criminal law and civil law often intersect or intersect. There are conditions where a criminal case also has a relationship with the civil aspect or vice versa in a civil case has a relationship with the criminal aspect. There is an overlap between the provisions of criminal law and civil law, especially when assets belonging to debtors are confiscated. The curator who exercises his authority often has to deal with investigators, especially if the assets included in the bankruptcy estate are also the object of criminal confiscation. The main problem in this study is how the intersection between the regulation of criminal confiscation and general confiscation and what is the legal position of bankruptcy assets as assets confiscated by the state in cases of corruption. Using normative juridical research methods using the legal approach (Statute Approach), conceptual approach (Conceptual Approach) and case approach (Case Approach). This research uses secondary data collected by the literature study method (Library Research) and then analyzed qualitatively. This provision gives rise to dualism in regulating the legal status of confiscated goods, because both bankruptcy law (private law) and criminal law (public law) both provide an imperative basis for confiscation. In Indonesia's positive law, criminal confiscation is prioritized even though it is temporary because it aims to ensure the availability of evidence. If the confiscated goods are confiscated for the state, the creditor cannot claim the right to them because they must be subject to a criminal verdict that prioritizes the public interest. On the other hand, if the goods are returned to the curator, then the settlement is continued through a general confiscation mechanism in accordance with bankruptcy law.